GENETIC PERSPECTIVES AND TREATMENT APPROACHES FOR PAEDIATRIC INHERITED BLOOD DISORDERS - ALI , H; KHAN , M; DIN , N; AZMATULLAH, M (Biological and Clinical Sciences Research Journal, 2024)
Inherited blood disorders, including thalassemia, haemophilia, and sickle cell anaemia, represent significant public health concerns in Pakistan. These genetic conditions, often exacerbated by high rates of consanguinity, contribute to significant childhood morbidity and mortality. The advent of genomics has facilitated a better understanding of the underlying genetic mutations, enabling more effective diagnosis and treatment options such as gene therapy and hematopoietic stem cell transplantation. This review focuses on the prevalence, genetic basis, and management of these disorders in Pakistan, exploring the unique challenges faced by the country's healthcare system and proposing public health strategies to address these challenges.